Lycium barbarum for Health and Longevity: A Review of Its Biological Significance - Tao Zhang; Elena-Alexandra Alexa; Gavin Liu; Alois Berisha; Rhys Walsh; Robbie Kelleher (Obesities)
Lycium barbarum (L. barbarum), commonly known as goji berry, is a functional food recognised for its diverse phytochemical composition and health benefits, particularly in metabolic health and disease prevention. This review explores its phytochemistry, focusing on polysaccharides, carotenoids, polyphenols, and alkaloids, which contribute to its extensive biological activities. L. barbarum polysaccharides, the primary bioactive components, exhibit antioxidant, immunomodulatory, and glycaemic-regulating properties, making them promising candidates for managing obesity-related metabolic disorders. Carotenoids, particularly zeaxanthin, play a key role in ocular health, while polyphenols and alkaloids enhance antioxidant, antimicrobial, and hepatoprotective effects. The biological properties of L. barbarum span metabolic health, cardiovascular function, and glycaemic control, alongside neuroprotection and cancer prevention. Its prebiotic effects on gut microbiota modulation offer additional benefits in managing obesity and associated complications. Furthermore, its antioxidant and anti-inflammatory activities support its role in alleviating oxidative stress and chronic inflammation, common in obesity and metabolic syndrome. Despite robust preclinical evidence, further studies are needed to validate its safety, efficacy, and long-term potential in human populations. This review highlights L. barbarum’s promising applications as a nutraceutical and therapeutic agent, particularly for metabolic and obesity-related health challenges.